Praktikalitas Lembar Kerja Siswa (LKS ) Berbasis Pendekatan Learning Cycle 5-Emateri Sistem Organisasi Kehidupan - Susanti, Diana; Indriati, Gustina; Yanti, Dilla Nurvivi (Universitas PGRI Sumatera Barat, 2017)
Â Teaching materials are part of all forms of written materials used to help the teachers in carrying out learning activities. A professional teacher is also required to produce teaching materials. Based on the observation, the teachers only utilize teaching materials in the form of a worksheet (LKS). LKS used for teaching is not in accordance with the curriculum needed and many images are not clearly visible. Thus, it has been developed teaching material in form of Student Worksheet (LKS) on Living Organizational System topic that has done validity test with validation result is 85.27% (criterion is very valid). For next, research to test the practicality which is a continued of the development stage. This research is a research development (Research and Development) with four D models. Data obtained are analyzed by descriptive analysis. From the result of the research, the value of practicality from teachers is 94,94% (very practical) and from a student is 87,01% (very practical). Then it can be concluded LKS based on learning cycle 5-e approach on Living Organization System topic developed is very practical.Â